Dear, Michael (2013). Why walls won’t work. Repairing the US-Mexico Divide - Oliveras González, Xavier (Documents d'Anàlisi Geogràfica, 2014)
Dear, Michael (2013). Why walls won’t work. Repairing the US-Mexico Divide New York: Oxford University Press, XIII + 270 p. ISBN 978-0-19-989798-8